التّعالق النّصّي في رواية (امرأة الغائب) لمهدي عيسى الصّقر - أسماء لصمر (My University, 2023)
Summary: Textual correlation imposed itself in a literary field, as it became a procedural tool for approaching and analyzing literary texts, to make it clear to us that there is no text written in isolation from what preceded it, as it bears traces of ancient texts that preceded it. The novel is formed from the phenomenon of textual interdependence, and the fictional text is formed from ancient narrative structures that meet in the form of mythical, epic, and religious platforms... to give the novel the characteristic of openness and semantic multiplicity. Hence our study in the novel "Woman of the Absent" by Issa Mahdi Al-Saqr, and we found that this novel is full of forms of textuality from different sources, and this indicates that the great creative ability of the novelist + we find that he tried to simulate ancient texts such as the epic of a thousand and one nights and the myth of Sisyphus, Circe and Lilith.. .to otherwise. He reproduced these texts in a new and different way that is in line with his creative method, which gave the text the characteristic of openness and its entry into new meanings. --------------------------- الملخص: فرض التّعالق النصي نفسه في حقل أدبي، حيث أضحى أداة إجرائيّة لمقاربة وتحليل النّصوص الأدبيّة، ليتّضح لنا أنّه ليس هناك نصّا يكتب بمعزل عمّا قبله فهو يحمل آثارا لنصوص قديمة سابقة عنه. وتتشّكل الرّواية من ظاهرة التّعالق النّصّي، ويتشكّل النص الرّوائي من بنيات سردية قديمة تلتقي على شكل مناصّات أسطورية، ملحميّة، دينيّة... لتمنح الرّواية صفة الانفتاح والتّعدد الدّلالي. ومن هنا كانت دراستنا في رواية "امرأة الغائب" لعيسى مهدي الصّقر، ووجدنا أنّ هذه الرّواية حافلة بأشكال تناصّية مختلفة المصادر، وهذا ذال على أنّ القدرة الإبداعيّة الكبيرة للرّوائي+ فنجده قد حاول محاكاة النّصوص القديمة مثل ملحمة ألف ليلة وليلة وأسطورة سيزيف وسيرس وليليث... إلى غير ذلك. هذه النّصوص أعاد إنتاجها بطريقة جديدة ومختلفة تتماشى مع طريقته الإبداعيّة ما منح النّص صفة الانفتاح ودخوله في معاني جديدة. -------------------- Résumé: La corrélation textuelle s'est imposée dans un champ littéraire, car elle est devenue un outil procédural d'approche et d'analyse des textes littéraires, pour nous faire comprendre qu'il n'y a pas de texte écrit isolément de ce qui l'a précédé, car il porte des traces de textes anciens qui l'ont précédé. il. Le roman est formé du phénomène d'interdépendance textuelle, et le texte de fiction est formé de structures narratives anciennes qui se rejoignent sous la forme de plates-formes mythiques, épiques et religieuses... pour donner au roman la caractéristique d'ouverture et de multiplicité sémantique. D'où notre étude dans le roman "Femme de l'absent" d'Issa Mahdi Al-Saqr, et nous avons constaté que ce roman regorge de formes de textualité provenant de différentes sources, et cela indique que la grande capacité créative de la romancière + nous constatons que il a essayé de simuler des textes anciens comme l'épopée des mille et une nuits et le mythe de Sisyphe, Circé et Lilith... autrement. Il reproduit ces textes d'une manière nouvelle et différente qui s'inscrit dans sa méthode de création, qui donne au texte la caractéristique de l'ouverture et de son entrée dans de nouvelles significations.